3D stochastic modeling of flow and solute transport in karst vadose zone. (December 2022) - Zeqiraj, Dulian
Abstract: Predicting the outcome of a natural process is extremely difficult and challenging. Processes in the vadose zone are complex and transport of contaminants to the aquifers has been the subject of many previous research and models. It is possible to estimate water and pollutant transport in the unsaturated zone with many models, from simple to complex, developed over the previous few decades. More and more subsurface researchers and managers are using these models in their work. For more complex nonlinear systems, modelers can use numerical codes to account for many nonlinear processes simultaneously. Although simple problems can still be handled analytically or semi-analytically, numerical models have become significantly more common in recent decades as computing power has improved on both personal computers and supercomputers. These numerical models are accurate and stable, and they are frequently parallelized as a consequence. For the modeling of solute transport in the vadose zone, stochastic-convective (parallel soil column) and stochastic-continuum processes have been proposed. Neither of these models tackles 3D stochastic modeling of flow and solute transport in karst zones, as far as we know. In this work we will use the PhreeqcRM that is a reaction module for transport simulators based on the geochemical model PHREEQC. Then we develope a unique flowchart for the transport and flow of contaminants in karst vadose zone. A Matlab script finally implements the flowchart.